Some Results for Certain Subclasses of Functions with Differential Equation and Subordination (European Journal of Pure and Applied Mathematics, 2012)
By applying the differential subordination theorem, we further investigate the subclassHn, [,] of functions which are analytic in the unit disk. Several subordination results on a convex function and a incomplete beta function are obtained. Moreover, the function that belongs to the Hn, [,] with a Cauchy-Euler differential equation is also discussed on similar subject. Our results extend some earlier works.